1971
DOI: 10.1002/pol.1971.150091107
|View full text |Cite
|
Sign up to set email alerts
|

Novel aliphatic polymers containing imide ring. I. Polyspiroimide based on methanetetraacetic acid

Abstract: synopsisHigh molecular weight polyspiroimides have been prepared by reacting diamines with the dianhydride of carboxymethanetetraacetic acid in polar organic solvents. Alternatively, thermal condensation of the preformed salt made from equimolar amounts of diamine and methanetetraacetic acid (MTA) can be used. These all-aliphatic polyimides are soluble in certain organic solvents, and possess good thermal-oxidative stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…1 PIs can be divided into two classes, aromatic and aliphatic. The first aromatic PI was developed and commercialised by DuPont™ in 1960 and aliphatic first reported in 1971 by Hirsch et al [2][3][4] Initially aromatic PIs were found to exhibit higher thermal, chemical and mechanical stabilities than aliphatic PIs, whereas, aliphatic PIs possess good solubility, low dielectric constant and high optical transparency owing to their molecular packing and polarisability. 5 PIs have found general use and application in the fields of aviation, aerospace, micro-electronics, gas separation, membranes, fuel cells, batteries, electronic memory devices, shape memory devices, optical devices, biomedical applications, sensors, aerogels and polymer matrices in composites/hybrid materials.…”
Section: Introductionmentioning
confidence: 99%
“…1 PIs can be divided into two classes, aromatic and aliphatic. The first aromatic PI was developed and commercialised by DuPont™ in 1960 and aliphatic first reported in 1971 by Hirsch et al [2][3][4] Initially aromatic PIs were found to exhibit higher thermal, chemical and mechanical stabilities than aliphatic PIs, whereas, aliphatic PIs possess good solubility, low dielectric constant and high optical transparency owing to their molecular packing and polarisability. 5 PIs have found general use and application in the fields of aviation, aerospace, micro-electronics, gas separation, membranes, fuel cells, batteries, electronic memory devices, shape memory devices, optical devices, biomedical applications, sensors, aerogels and polymer matrices in composites/hybrid materials.…”
Section: Introductionmentioning
confidence: 99%